RESULTS OF PREVENTIVE MEASURES IN PRESCHOOL CHILDREN - L.F. Kaskova; M.O. Sadovski (Український стоматологічний альманах)
The prevalence and intensity of the carious process increases with age and leads to disorders of the maxillofacial area due to the formation of incorrect functions (chewing, speech) that occur as a result of the destruction and early removal of temporary teeth in children. Filling of molars fissures, which involves isolating the most vulnerable areas of the occlusal surface from the action of external cariogenic factors, occupies a prominent place among various methods of caries prevention in terms of effectiveness.